Coronavirus Disease 2019 Outbreak in a Psychiatric Closed Ward: What We Have to Learn - Chun, June Young; Jun, Jin Yong; Choi, Jiah; Jo, Minho; Kwak, Kyongmin; Jeong, Yunjin; Lee, Junsoo; Park, Junkyu; Lee, Kang Hee; Nam, Yoonyoung; Choi, Young Ju; Lee, Young Moon; et al. (Frontiers in Psychiatry, 2021)
An outbreak of COVID-19 with an extremely high attack rate happened in a psychiatric closed ward. One hundred two (98.1%) out of 104 patients were diagnosed with COVID-19 between February 20th and 26th, 2020, most of whom were with schizophrenia. Facility factors (such as multi-share rooms, closed windows, and absence of alcohol hand rubs), along with chronic medical conditions, and difficulty to explain symptoms for psychiatric patients might have contributed to the high attack rate. To overcome these hurdles, efficient ventilating with filtration system in psychiatric facilities, strict access control to closed wards, and prompt response to febrile patients could prevent nosocomial outbreak. We must consider that the influx of COVID-19 into a closed ward could cause an extremely high attack rate, and have to be vigilant against COVID-19 in psychiatric wards.